Combination of pH adjusting and intermittent feeding can improve fermentative acetone-butanol-ethanol (ABE) production from steam exploded corn stover. (November 2022) - Su, Changsheng; Zhang, Changwei; Wu, Yilu; Zhu, Qian; Wen, Jieyi; Wang, Yankun; Zhao, Jianbo; Liu, Yicheng; Qin, Peiyong; Cai, Di
Abstract: Steam explosion (SE) is an effective and industrially scalable lignocellulose pretreatment method that can be used for second-generation acetone-butanol-ethanol (ABE) fermentation. Nevertheless, a series technical barrier including the high inhibitors content in hydrolysate, and low concentration and low yield of ABE production always hindered the availability of the SE technique. In this study, aiming to solve the above obstacles and boosting cellulosic ABE production, the ABE fermentation process was intensified by a novel fed-batch strategy that combined the pH adjusting with intermittent feeding. Results revealed that maintaining the pH at 6.5 for initial 12 h of cultivation ensures the smoothly shifting of the acidogenesis phase to solventogenesis phase of the C. acetobutylicum cells, so that avoided the acid crash. While the lag period of fermentation was obvious shorted by intermittent feeding the concentrated SE hydrolysate into the dilute broth. Consequentially, 17.75 g/L of ABE (containing 11.75 g/L of butanol) can be obtained after 48 h of inoculation, with the yield and productivity of ABE were 0.36 g/g (of sugars) and 0.37 g/L‧h, respectively. Correspondingly, 194.9 g of ABE (including 129.0 g of butanol) can be produced from 1 kg of dried corn stover. Therefore, the novel process intensifying method could obviously improve the biobutanol production, which showed high potential and applicability in large-scale ABE productions.